Duração do sono e excesso de peso em adolescentes de 10 a 14 anos: a dieta é mediadora? - Santos, Elaine Valdna Oliveira dos (2018)
Objective: To evaluate the association between short sleep duration and overweight in adolescents and whether diet acts as a mediator. Methodology: A cross-sectional study was carried out in which 1384 adolescents participating in the Longitudinal Study on Sedentary Behavior, Physical Activity, Eating Habits and Adolescent Health (LONCAAFS) were evaluated. Information was obtained regarding sociodemographic data, class shift, sleep duration, nutritional status, sedentary behavior and food consumption. For the statistical analysis, the Chi-Square Test, Logistic Regression and Mediation Analysis were performed, using the Mediation software package R, which considers the total direct and indirect effects of the relationship between duration of sleep and overweight of adolescents. The results were stratified by course period. Results: A mean sleep duration of 9.6 hours was recorded, and 29.5% of the adolescents presented short duration (<9h/night). There was no statistically significant relationship between sleep duration and overweight (no stratification by course period: OR=0,9840 IC=0,8997; 1,0762; morning/full-time: OR=0,9482 IC=0,8170; 1,1005, afternoon: OR=1,0035 IC=0,8957;1,1243) or between sleep duration and diet (without stratification by course period: β=7,1392 p=0,81; morning/full-time: β= -3,0738 p=0,93; afternoon: β=31,1476 p=0,54) or diet and excess weight (without stratification by course period: OR=0,9998 IC=0,9995; 1,0000; morning / full-time: OR=0,9999 IC=0,9993;1,0000, afternoon: OR=0,9997 IC=0,9993; 1,0000). There was no effect of total sleep duration on overweight (without stratification by course period: β = -0,0352 IC= -0,0998; 0,03; morning/full-time: β = -0,0193 IC= -0,1049; 0,06; afternoon: β = -0,0500 IC= -0,1529; 0,05) direct effect (without stratification by course period: β= -0,0348 IC= -0,0996; 0,03; morning/full-time: β= -0,0195 IC= -0,1029; 0,06; afternoon: β = -0,0481 IC= -0,1513; 0,05) or medium (without stratification by course period: β = -0,0004 IC= -0,0046; 0,00; morning/ full-time: β=0,0002 IC= -0 ,0053; 0,01; afternoon: β = -0,0019 IC= -0,0137; 0,01). Conclusion: In the initial phase of adolescence, overweight was not influenced by the short sleep duration, and the diet had no mediating role.